Proficiency at using the metered dose inhaler among patients attending the Witpoort Hospital Outpatient Clinic - Isiguzo, O. F. (University of Limpopo (Medunsa Campus), 2011)
AIM AND OBJECTIVE: To determine metered dose inhaler usage technique among asthmatic patients attending outpatient clinic and assess relationship between proficiency and specific factors for efficient or non-efficient usage. DESIGN: A cross-sectional study was conducted in outpatient clinic; the inhalation technique was assessed in six steps. SETTING: outpatient clinic of Witpoort hospital, Limpopo province, South Africa. RESULT: Total of 102 patients (32 male and 70 female) was assessed with age ranging from 10 to 77(mean 44) between September to November 2008. Only three (2.9%) of patients could perform all six steps correctly. Percentage of patients performing each step correctly were: 20.6% , 65.7%, 4.9%, 4.9% and 1% got none of the step, one step, two steps, three steps, and four steps correctly respectively. None got up to five steps correctly. The 2.9% that got all six steps correctly were taught by a doctor and had asthma duration of greater than five year. CONCLUSION: This study shows a high level of incorrect usage of metered dose inhaler among asthmatic patient attending witpoort hospital. Sex (gender), age and educational level did not play a role in proficiency of inhaler use.
Thesis (M Med (Family Medicine))--University of Limpopo (Medunsa Campus), 2011.
Keywords: Asthma; Inhalation